2007
DOI: 10.1111/j.1365-2621.2007.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Spoilage potential of ice‐stored whole musky octopus (Eledone moschata)

Abstract: The spoilage potential of fresh musky octopus (Eledone moschata) was determined by evaluating the changes in biochemical and physical properties, microbial growth and sensory quality of the mantle and tentacles, over a period of 18 days. Whole musky octopus, stored in melting ice from the time of harvest, had a storage life of 10 days. Early deterioration in the sensory quality resulted primarily from autolytic reactions. Pseudomonas spp. dominated the spoilage flora, reaching an average count of 10 8 CFU g )1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Meanwhile, a significant increase (P < 0.05) was recorded in pH of frozen squids (8.0±0.01). This value was within the observed range in other studies by Albanese et al (2005) and Lougovois et al (2007) who noticed that freezing caused a significant increase of pH in different cephalopods. They attributed that to the rapid spoilage of the product and the formation of alkaline compounds of autolysis and bacterial metabolites in the muscles.…”
Section: Chemical Qualitysupporting
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, a significant increase (P < 0.05) was recorded in pH of frozen squids (8.0±0.01). This value was within the observed range in other studies by Albanese et al (2005) and Lougovois et al (2007) who noticed that freezing caused a significant increase of pH in different cephalopods. They attributed that to the rapid spoilage of the product and the formation of alkaline compounds of autolysis and bacterial metabolites in the muscles.…”
Section: Chemical Qualitysupporting
confidence: 77%
“…However, in general few studies on cephalopods quality were directed mostly to the squid (Ruíz-Capillas et al, 2002a&b;Albaneses et al, 2005) and Octopus (Lougovois et al, 2007;Atrea et al, 2009). Therefore, from the nutritional point of view, the objectives of this research are: 1-Comparison of the chemical (pH, trimethylamine and volatile base nitrogen) and biochemical composition of the most commonly consumed fresh chilled cephalopods in the Suez Canal area with the imported frozen squid in the market.…”
Section: Introductionmentioning
confidence: 99%
“…4). The increase was attributed to the production of ammonia due to the bacterial deamination of proteins, amino acids and other basic nitrogenous compounds in the flesh of cephalopods (Lougovois et al 2008). Paarup et al (2002) reported an increase in ammoniacal nitrogen of squids stored in ice similar to this finding.…”
Section: Biochemical Qualitysupporting
confidence: 68%
“…In support of our findings, Barbosa and Vaz-Pires (2003) perceived slightly unpleasant odour in ice stored octopus between days 4 and 5, which later became unacceptable on day 8. Lougovois et al (2008) observed sour and rotten odour but not ammoniacal odour during the spoilage of whole musky octopus stored in ice. As the octopus stored in ice was wrapped in polythene bags, the ammonia liberated due to autolytic degradation might have got trapped within the bags instead of getting dissolved in ice water and this had lead to the formation of ammoniacal odour.…”
Section: Sensory Qualitymentioning
confidence: 99%
See 1 more Smart Citation